CYP2D6 in the Brain: Potential Impact on Adverse Drug Reactions in the Central Nervous System—Results From the ADRED Study - Just, Katja S.; Dormann, Harald; Freitag, Mathias; Schurig, Marlen; Böhme, Miriam; Steffens, Michael; Scholl, Catharina; Seufferlein, Thomas; Graeff, Ingo; Schwab, Matthias; Stingl, Julia C. (Frontiers in Pharmacology, 2021)
Cytochrome P450 (CYP) 2D6 is a polymorphic enzyme expressed in the central nervous system (CNS), important in drug metabolism and with a potentially constitutive role in CNS function such as vigilance. This study aimed to analyze variability in CYP2D6 activity linked to vigilance-related adverse drug reactions (ADR) in the CNS. A dataset of N=2939 ADR cases of the prospective multi-center observational trial in emergency departments (ED) (ADRED; trial registration: DRKS-ID: DRKS00008979) was analyzed. Dizziness as the most frequent reported CNS ADR symptom (12.7% of patients, n=372) related to vigilance was chosen as outcome. The association of dizziness with CYP2D6 activity markers was analyzed. The number of CYP2D6 substrates taken, a CYP2D6 saturation score (no, moderate, and strong saturation), a CYP2D6 saturation/inhibition score (no, weak, moderate, and strong), and composed CYP2D6 activity using a genotyped subsample (n=740) calculating additive effects of genotype and CYP2D6 saturation by drug exposure, were used as CYP2D6 activity markers. Effects were compared to other frequent non-vigilance-related CNS ADR symptoms (syncope, headache). Secondary analyses were conducted to control for other ADR symptoms frequently associated with dizziness (syncope, nausea, falls). The majority of all patients (64.5%, n=1895) took at least one drug metabolized by CYP2D6. Around a third took a CNS drug (32.5%, n=955). The chance to present with drug-related dizziness to the ED increased with each CYP2D6 substrate taken by OR 1.11 [1.01 – 1.23]. Presenting with drug-related dizziness was more likely with CYP2D6 saturation and saturation/inhibition (both OR 1.27 [1.00 – 1.60]). The composed CYP2D6 activity was positively associated with dizziness (p=0.028) while poorer activity affected patients more often with dizziness as an ADR. In contrast, non-vigilance-related ADR symptoms such as syncope and nausea were not consistently significantly associated with CYP2D6 activity markers. This study shows an association between the number of CYP2D6 substrates respective, the predicted CYP2D6 activity and the occurrence of dizziness as an CNS ADR symptom. As dizziness is a vigilance-related CNS symptom, patients with low CYP2D6 activity might be more vulnerable to drug-related dizziness. This study underlines the need for understanding individual drug metabolism activity and individual risks for ADRs.